Anisotropy estimation of compacted municipal solid waste using pressurized vertical well liquids injection. Issue 6 (June 2014) - Singh, Karamjit; Kadambala, Ravi; Jain, Pradeep; Xu, Qiyong; Townsend, Timothy G
Waste hydraulic conductivity and anisotropy represent two important parameters controlling fluid movement in landfills, and thus are the key inputs in design methods where predictions of moisture movement are necessary. Although municipal waste hydraulic conductivity has been estimated in multiple laboratory and field studies, measurements of anisotropy, particularly at full scale, are rare, even though landfilled municipal waste is generally understood to be anisotropic. Measurements from a buried liquids injection well surrounded by pressure transducers at a full-scale landfill in Florida were collected and examined to provide an estimate of in-situ waste anisotropy. Liquids injection was performed at a constant pressure and the resulting pore pressures in the surrounding waste were monitored. Numerical fluid flow modeling was employed to simulate the pore pressures expected to occur under the conditions operated. Nine different simulations were performed at three different lateral hydraulic conductivity values and three different anisotropy values. Measured flowrate and pore pressures collected from conditions of approximate steady state were compared with the simulation results to assess the range of anisotropies. The results support that compacted municipal waste in landfills is anisotropic, provide anisotropy estimates greater than previous measurements, and suggest that anisotropy decreases with landfill depth.